Performance evaluation of silicoaluminophosphate with SFO topology for water-sorption-driven heating and cooling systems. (5th November 2022) - Liu, Zhangli; Xu, Min; Huang, Caifeng; Huai, Xiulan
Highlights: Stable SAPO-SFOs with large microporosity of 0.22–0.28 ml g −1 are hydrothermal synthesized. The SAPO-SFOs show excellent water–adsorption performance of 0.24–0.28 g g −1 at P/P 0 = 0.2 and low regeneration temperature. The coefficients of performance of water-based sorption system employing SAPO-SFO with 7 wt% Si are evaluated as 0.86 for cooling and 1.76 for heating. The water adsorption mechanism of SAPO-SFOs is explored. Abstract: Low-grade thermal-driven water-based sorption chillers and heat pumps are promising strategies to realize the near-zero-carbon target. However, developing excellent-performance water-sorption materials driven by ultralow-temperature thermal energy is still a key issue. In this study, silicoaluminophosphate with SFO topology (SAPO-SFO) synthesized by hydrothermal method is proposed as a more-effective adsorbent for water-based sorption applications. SAPO-SFO exhibits large micropore volume of 0.22–0.28 ml g −1, high water uptake of 0.24–0.28 g g −1 at P/P 0 = 0.2, low regeneration temperature, and excellent hydrothermal stability. Importantly, the water-based sorption applications employing SAPO-SFO with 7 wt% Si achieve extremely high coefficients of performance of 0.86 for cooling and 1.76 for heating at low-driven temperatures of 64 °C and 82 °C, respectively. Furthermore, the mechanism of water adsorption for SAPO-SFO is revealed as that large purely siliceous regions and defects induced by uneven silicon insertion result in low enthalpy of adsorption. These results make SAPO-SFO a potential high-performance and ultralow-temperature thermal driven porous material for water-based sorption applications.